"Picturephone in My Home": Actor-Network Theory and Foucauldian Discourse Analysis on Northern Finnish Older Adults Starting to Use a Video Conferencing Service. Issue 2 (30th December 2020) - Outila, Marjo; Kiuru, Hilla
Abstract: Technology has been considered an important means to deliver services in a cost-effective manner in societies that are aging and implementing austerity policies. In this article, we analyze older adults' use of assistive technology, the picturephone, in home care by combining actor-network theory (ANT) and Foucauldian discourse analysis (FDA). We also apply Foucault's concepts of technologies of the self, regimen, and resistance. Our research materials consist of interviews with eight Northern Finnish older adults and observation data. According to our results, technological translation takes place when users associate picturephone technology with the discourses on health and safety, connectedness, and/or learning. When the technology discourse collides with or deviates from these discourses, it disrupts the technological translation, and older adults do not include the picturephone technology in their regimen, their daily life. In Finland, care policy favors technology and pursues its adoption in older adults' care. In our case, private companies, care workers, technology advisers, family members, and older adults are recruited to join this effort. Older adults' position in their social-material networks varies strongly in the different phases of the translation, and their technologies of the self have a significant effect on its outcome. This should be considered when designing and utilizing ICT technologies in elderly care.